Log periodic dipole array antenna for UHF band application: article / Shazrol Basri - Basri, Shazrol (2010)
This project presents the design of a microstrip log periodic dipole antenna. The antenna is designed for a center frequency of 2.4 GHz with 45% operating bandwidth for VSWR < 2. CST simulation software is fully utilized to simulate the response of return loss, VSWR, radiation pattern and gain. The antenna was designed to cover the standard frequency of IEEE 802.11 b/g (2.4-2.4835GHz), WiMAX (2.33.6GHz) and Wi-Fi of 2.4GHz band. This dipole antenna was fabricated on FR4 substrate with the dielectric constant of εr=4.9 and thickness t=1.6mm. Both simulated and measured results are compared, analyzed and presented in this paper.